STRUKTUR FILM (Struktur Film Eiffel... I’m in Love) - Budiman Akbar (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
In story telling a film has a structure that has been generally done by Hollywood and until now still valid, even reaching out to the whole world. Hollywood has been doing so since the year 1910, which continues to grow until it is said to be perfect in the era of voiced movies. Films that use story structures of the era can achieve success. The films that achieve the success in question, is a movie that reaches the number of spectators is quite fantastic, which is now known as the movie box office. The influence of the story structure in films is, in fact, one of the film's main filmmaking strategies. The structure of the Hollywood story is one of Hollywood's movie formats, which David Bordwell says are known as the Classical Hollywood Structure.